Design of a logistics performance management system based on the system dynamics model. Issue 3 (22nd October 2019) - Irfani, Dian Prama; Wibisono, Dermawan; Basri, Mursyid Hasan
Abstract : Purpose: Logistics systems used in companies that perform multiple roles are expected to be able to manage conflicting objectives. Nevertheless, the literature suggests that many existing logistics performance measurement system (PMS) frameworks are not optimized to provide mechanisms to reveal dynamic relationships between conflicting performance indicators. The purpose of this paper is to develop a new logistics PMS by linking the system dynamics model with a set of balanced performance indicators. Design/methodology/approach: The logistics PMS is developed through a literature review and case study of a company that plays multiple roles. The interrelationships between logistics factors and their links to end results are modeled in diagrams through in-depth interviews with stakeholders. The developed model is then used to build a simulation tool to analyze factors that cause poor performance. Findings: The new logistics PMS developed by incorporating system dynamics offers decision makers ways to identify dynamic relationships among factors and conflicting indicators, in turn helping them to understand holistic logistics performance, objectively analyze why logistics systems perform in a certain way and foster a common shared view. Practical implications: Stakeholders of companies that play multiple roles can use the new PMS model to comprehensively evaluate the performance of logistics systems. In addition, the increased visibility of logistics systems may support decision-making while preventing local optimization. Originality/value: A logistical PMS based on the system dynamics model for managing logistics systems in companies performing multiple roles has not yet been identified. This paper fills this theoretical gap and contributes to the academic literature by proposing a novel PMS model based on the system dynamics model to address the limitations of existing PMS frameworks.